Effect of venture capital investment horizon on new product development: Evidence from the medical device sector - Shin, Moonsik; Bae, Joonhyung; Ozmel, Umit (Journal of Business Venturing, 2025)
Drawing on entrepreneurial financing literature, we investigate how venture capital (VC) firms' investment horizons affect their ventures' product quality problems. We argue that when a VC firm has a short investment horizon, it may guide its portfolio companies to develop new products fast to increase the likelihood of successful exits. However, this deliberate effort may act as a double-edged sword for ventures. That is, VC firms' guidance on product commercialization could inadvertently expose ventures to product quality problems. Building on this notion, we suggest that ventures backed by VC firms with short investment horizons may experience more product quality problems than those backed by VC firms with long investment horizons. We further suggest that the effect of a VC firm's investment horizon on product quality problems is mitigated when the venture is invested by corporate VC investors but amplified when the venture develops complex products. We test our hypotheses using a dataset on product recalls of VC-backed ventures in the U.S. medical device industry. Executive summary The success and survival of new ventures largely depend on their ability to develop and commercialize innovative products. Due to their limited resources, these ventures often seek support from venture capital (VC) investors. However, the involvement of VC investors can be a double-edged sword, as their focus on timely (or even accelerated) product introduction may lead to unforeseen problems. This occurs because VC firms may adopt different approaches to supporting ventures in new product development, depending on their investment horizons, which are constrained by their contractual obligations to their limited partners (LPs). Specifically, VC firms with long investment horizons may allow their portfolio companies to have sufficient time to develop new products. In contrast, VC firms with short investment horizons may be under time pressure and guide their portfolio companies to speed up the product development process to increase the chances of ventures' exits within a limited timeline. Building on this notion, we examine how the investment horizons of VC investors impact ventures' product quality problems. Ventures invested by VC firms with short investment horizons may face pressure to accelerate the new product development process, preventing the ventures from engaging in time-intensive learning processes necessary for cultivating new technological and market knowledge. Therefore, we propose that ventures invested by VC firms with short investment horizons may experience more product quality problems than those invested by VC firms with long investment horizons. We further propose two boundary conditions to validate our theoretical mechanisms. First, we suggest that the negative effect of VC investors' time horizons on product quality problems is mitigated by the presence of corporate VC (CVC) firms in the investment syndicate. As CVC firms have long investment horizons and pursue strategic goals, they can counterbalance the influence of VC firms with short investment horizons on ventures' product development process. Second, we suggest that the complexity of the products developed by ventures amplifies the impact of VC firms' investment horizons on product quality problems. This is because complex products require more time for intensive learning and information processing, making ventures particularly susceptible to product quality problems when under time pressure. To test these arguments, we use the data on product recalls of VC-backed ventures in the U.S. medical device industry. We also incorporate insights from interviews with venture capitalists and entrepreneurs to validate our arguments. This study enhances our understanding of how partner-specific characteristics (VC firms' investment horizons in our context) affect private ventures' development paths and outcomes. By highlighting the tradeoffs associated with VC funding, we provide a more balanced perspective to the literature on VC investments, which has predominantly emphasized the benefits of VC investment. Our arguments and findings suggest that the time pressure faced by VC investors can be transferred to ventures, potentially resulting in unexpected product quality problems.